2014
DOI: 10.2463/mrms.2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Ménière’s Disease after Combined Intratympanic and Intravenous Injection of Gadolinium using HYDROPS2

Abstract: Endolymphatic hydrops (EH) in Ménière's disease is currently evaluated by 3-dimensional (3D)-real inversion recovery (IR) sequence after intratympanic (IT) administration of gadolinium (Gd) or by heavily T 2 -weighted (hT 2 W)-3D-fluid-attenuated IR (FLAIR) sequence after intravenous (IV) injection of Gd. Unilateral IT injection is usually performed. We employed a method in which we simultaneously administered contrast into one ear intravenously (IV side) and into the other ear both intravenously and intratymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Only HYDROPS images were able to demonstrate EH in all ears VEH and cEH were demonstrated in 89% and 67% of ears, respectively. A significant rate of vEH (55%) and cEH (44%) was also found in the contralateral asymptomatic ears 27 .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Only HYDROPS images were able to demonstrate EH in all ears VEH and cEH were demonstrated in 89% and 67% of ears, respectively. A significant rate of vEH (55%) and cEH (44%) was also found in the contralateral asymptomatic ears 27 .…”
Section: Resultsmentioning
confidence: 80%
“…The presence of EH in the contralateral asymptomatic ears was demonstrated by Lida et al by using both IT and IV administration: 67% of asymptomatic ears were shown to have both vEH and cEH 26 . A comparison between the results obtained after simultaneous IV-IT administration was made by Naganawa et al, by using 3D-real IR images for IT-IV side and HYDROPS2 for IV 27 . Only HYDROPS images were able to demonstrate EH in all ears VEH and cEH were demonstrated in 89% and 67% of ears, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…HYDROPS2 imaging can evaluate both the IV-only side and the IT ? IV side simultaneously [66] (Fig. 2).…”
Section: Intratympanic and Intravenous Injection Of Gbcm (It ? IV Doumentioning
confidence: 97%
“… 13 In contrast, HF enables the detection of endolymphatic hydrops after a single dose of intravenous gadolinium-based contrast agent in patients with Ménière’s disease. 14 23 …”
Section: Introductionmentioning
confidence: 99%